Ophthalmologic and facial abnormalities of Nicolaides-Baraitser syndrome. (3rd September 2022) - Simmers, Russell; Goodwin, Allison; Al Saif, Hind; Couser, Natario
ABSTRACT: Background: Nicolaides-Baraitser syndrome (NCBRS), first described in 1993, is a rare autosomal dominant disease caused by pathogenic variants in the SMARCA2 gene on chromosome 9p24.3. NCBRS typically presents with dysmorphic facial features, seizures, intellectual disability, and developmental delays. Abnormal findings of the eye and ocular adnexa associated with NCBRS have not been systematically evaluated and summarized in literature. This report presents the case of a 4-year-old male with NCBRS along with a systematic review of literature of the abnormal ophthalmologic and facial features of NCBRS cases. Methods: A systematic review of literature of published cases of molecularly confirmed NCBRS was performed and the frequencies of eye, ocular adnexa, and facial abnormalities were calculated. Results: Our patient's abnormal eye features include myopia, down slanting palpebral fissures, sagging inferior periorbital skin, hypertelorism, and long eyelashes. From the systemic review of literature, the most common abnormal eye and ocular adnexa features include prominent/long eyelashes, thick eyebrows, sagging periorbital skin, down slanting palpebral fissures, and ptosis. The most common facial dysmorphic features include thick/everted lower lip, coarse facial features, wide/large mouth, and thin upper lip. Dental abnormalities are also commonly reported. Conclusions: NCBRS frequently presents with well-defined ophthalmic and facial abnormalities. Prompt ophthalmologic evaluation following NCBRS diagnosis may be recommended to screen for several eye disorders. Surgical correction of ptosis may be indicated for NCBRS patients. This report may help further delineate the phenotype of this condition, which may allow for more rapid identification of those affected and provide incentive for additional studies.